Analysis Effect of Psychological Factors on Work Productivity in Iron and Steel Industry - Alamulyaqin Romadloni; Mirna Apriani; Indri Santiasih (Indonesian Journal of Innovation Multidisipliner Research, 2024)
The processing of iron and steel requires a heating temperature of up to 900 degrees Celsius. Psychological factors will have an impact on work productivity and make workers very uncomfortable. We involved 15 respondents in the area of the short taper and eye forming process and tested the work environment and conducted a stress level survey on the respondents. The results of the analysis above measuring psychological factors on 15 respondents, the Shearing Process section (Taper and Eye Forming) found that the 6 triggers of work stress were within moderate limits (10-24). With the most dominant aspect of potential stress, namely Qualitative Overload. It is necessary to add hours of rest for workers to control the level of work stress in workers.